A systems biology study on NF[kappa]B signaling in primary mouse hepatocytes - Pinna, Federico; Sahle, Sven; Beuke, Katharina; Bissinger, Michaela; Aydin, Selcan; D'Alessandro, Lorenza; Gauges, Ralph; Raue, Andreas; Timmer, Jens; Klingmüller, Ursula; Schirmacher, Peter; Kummer, Ursula; et al. (Frontiers in physiology, 2012)
The cytokine tumor necrosis factor-alpha (TNFα) is one of the key factors during the priming phase of liver regeneration as well as in hepatocarcinogenesis. TNFα activates the nuclear factor κ-light-chain-enhancer of activated B cells (NFκB) signalling pathway and contributes to the conversion of quiescent hepatocytes to activated hepatocytes that are able to proliferate in response to growth factor stimulation. Different mathematical models have been previously established for TNFα/NFκB signalling in the context of tumor cells. Combining these mathematical models with time resolved measurements of expression and phosphorylation of TNFα/NFκB pathway constituents in primary mouse hepatocytes revealed that an additional phosphorylation step of the NFκB isoform p65 has to be considered in the mathematical model in order to sufficiently describe the dynamics of pathway activation in the primary cells. Also, we addressed the role of basal protein turnover by experimentally measuring the degradation rate of pivotal players in the absence of TNFα and including this information in the model. To elucidate the impact of variations in the protein degradation rates on TNFα/NFκB signalling on the overall dynamic behaviour we used global sensitivity analysis that accounts for parameter uncertainties and showed that degradation and translation of p65 had a major impact on the amplitude and the integral of p65 phosphorylation. Finally, our mathematical model of TNFα/NFκB signalling was able to predict the time course of the complex formation of p65 and of the inhibitor of NFκB (IκB) in primary mouse hepatocytes, which was experimentally verified. Hence, we here present a mathematical model for TNFα/NFκB signalling in primary mouse hepatocytes that provides an important basis to quantitatively disentangle the complex interplay of multiple factors in liver regeneration and tumorigenesis.